Pelatihan Budidaya Jamur Keberuntungan Abadi (JAKABA) Sebagai Pupuk Tanaman di Sekolah Dasar - Firdaus Yuni Dharta; Suhartini Khalik; Hazairin Nikmatul Lukma; Eri Ester Khairas; Estu Widarwati; Siti Nurhayati; Riastuti Kusuma Wardani; Nana Meily Nurdiansyah; Ika Purnama Sari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This community service project aimed to educate elementary school students on sustainable agriculture through hands-on training in cultivating oyster mushrooms (Pleurotus ostreatus) using JAKABA—a fermented mixture of coconut water and banana stem—as an organic growing medium and fertilizer. The training involved 15 students from grades 4 and 5 at Budi Mulya Elementary School and was conducted over two weeks using participatory and experiential learning methods. Results from pre- and post-training assessments indicated a significant increase in students’ knowledge about organic waste utilization, mushroom cultivation, and the benefits of JAKABA. The students showed high engagement and enthusiasm, with over 90% expressing interest in continuing the practice at home. Mushroom growth success reached 90%, demonstrating the effectiveness of JAKABA as a sustainable medium.The program successfully integrated environmental awareness, scientific learning, and life skills education. It also promoted character development and entrepreneurship among young learners. This initiative serves as a replicable model for environmentally-based learning in elementary education.